LOCALIZAÇÃO DE ONTOLOGIAS – ELEMENTOS PARA A CONSTRUÇÃO DE UMA ABORDAGEM - Silva, Manuel Moreira da (2019)
The development of robust multilingual resources to meet the growing demands of intra and inter-organizational complexity is a complex process that demands an increase of quality in the organizations’resource interaction and sharing modes, trough, for example, stronger involvement of different stakeholders in effective and innovative collaboration ways. It is a process where several problems and difficulties arise, such as, in the creation of multilingual lexical databases, the development of an architecture capable of addressing a wide range of language issues such as polysemy, lexicalization patterns or equivalence in translation. These questions appear also in the construction of terminological resources or multilingual ontologies. In the construction of a multilingual ontology, the questions and their complexity increases, given the nature and purposes of the semantic artifact, of the elements to localize (concepts and conceptual relations) and the context in which the localization process occurs. We intend in this article to analyze the concept and the localization process in the context of ontology-based knowledge management systems, taking into account the central role of terminology in the localization process, the different approaches and models proposed and the existing linguistic tools that support the implementation process. Finally we will try to establish some parallels between the traditional localization process and the ontologies localization process to better contextualize and define it.